Quản trị nguồn nhân lực xanh và hành vi thân thiện với môi trường của nhân viên khách sạn cao cấp: Khoảng trống thái độ - hành vi và vai trò điều tiết của áp lực thời gian - Vũ Tuấn, Dương; Vũ Văn, Hùng; Nguyễn Mạnh, Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Through applying the theory of social identity and green human resource management, the research has tested hypotheses reflecting the role of green human resource management on environmental and pro-environmental behaviour. The results of SEM model analysis from survey data of 323 employees working in luxury hotels in Hanoi have demonstrated the promotion ability of green human resource management practices to environmental attitude and pro-environmental behaviour of employees. The study also proves that there exists a gap between employees' environmental attitudes and pro-environmental behaviour, and this gap is partly explained by time pressure. Finally, the results were discussed and some implications were suggested for managers to promote pro-environmental behaviour of employees.